Identification and classification of brownfield locations in Danube region in Serbia - Lojaničić, Damjana R (Arhitektura i urbanizam, 2018)
The identification and classification of brownfield locations in the territory of seven settlements in Danube region in Serbia are presented in the paper from the aspect of the adaptive reuse regeneration method. Identification of brownfield locations is based on analysis of different plans, strategies of sustainable development and existing databases. This locations are classified according to original uses of existing buildings and planned uses. The classification is based on analysis of proper parts of plans for each settlement which refer to existing and predominantly planned uses. The objectives of research аre related to creating an overview of locations for potential investments which allows further researches and access to regeneration projects that realize concurrently, which is of significance for development of Danube region in Serbia, generally. By classification, the research is directed to reconsideration of uses planning process(urbanistic aspect), compatibility of uses and selection of regeneration method for the buildings which are out of use (architectural aspect).